Immunization dropout rate and data quality among children 12-23 months of age in Ghana - Benjamin Baguune; Joyce Aputere Ndago; Martin Nyaaba Adokiya (BMC, 2017)
Abstract Background Immunization against diseases is one of the most important public health interventions with cost effective means to preventing childhood morbidity, mortality and disability. However, a proportion of children particularly in Africa are not fully immunized with the recommended vaccines. Thus, many children are still susceptible to the Expanded Program on Immunization (EPI) targeted diseases. The objective of this study was to determine the immunization dropout rate and data quality among children aged 12-23 months in Techiman Municipality, Ghana. Methods A cross-sectional cluster survey was conducted among 600 children. Data was collected using semi-structured questionnaire through face-to-face interviews. Before the main data collection, the tools were pre-tested in three different communities in the Municipality. The mothers/caregivers were interviewed, extracted information from the child immunization cards and observation employed to confirm the presence of Bacillus Calmette-Guerin (BCG) scar on each child. Routine immunization data was also extracted from immunization registers and annual reports in the Municipality. Results Immunization coverage for each of the fifteen vaccines doses is above 90.0% while full childhood immunized status is 89.5%. Immunization dropout rate was 5.6% (using BCG and Measles as proxy vaccines). This is lower than the 10.0% cutoff point by World Health Organization. However, routine administrative data was characterized by some discrepancies (e.g. > 100.0% immunization coverage for each of the vaccines) and high dropout rate (BCG - Measles = 31.5%). Binary regression was performed to determine predictors of dropout rate. The following were statistically significant: married (OR = 0.31; 95% = CI 0.15-0.62; and p = 0.001), Christianity (OR = 0.27; 95% CI = 0.13-0.91; and p < 0.001), female child (OR = 0.50; 95% CI = 0.26-0.91; and p = 0.024) and possession of immunization card (OR = 50.3; 95% CI = 14.40-175.92; and p < 0.001) were found to be associated with immunization dropout. Conclusion Childhood full immunized status (89.5%) and immunization coverages (>90%) are high while dropout rate is lower than the recommended cutoff point by WHO. However, immunization data quality remains inadequate. Thus, health education and orientation of service providers is urgently needed. In addition, immunization registers and data quality are issues that require attention.